2007
DOI: 10.4314/eamj.v83i10.9464
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomiasis presenting as acute appendicitus

Abstract: Background: Schistosomiasis is a chronic granulomatous inflammation that affects many systems in the body including the gastrointestinal tract. This study was carried out by reviewing all cases of schistosomal appendicitis, and documents any association with acute appendicitis. Conclusion:This finding has demonstrated that though the frequency of appendix involvement is low considering the endemicity of schistosomiasis in our environment, however acute appendicitis may be caused by schistosomiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 8 publications
1
44
0
Order By: Relevance
“…[4] The incidence of schistosomal appendicitis is 0.02-6% in endemic areas but its very rare in developed countries. [5,6] Studies where schistosomiasis is endemic, have shown appendicitis to be relatively uncommon and the cause is not usually attributable to a schistosomal infestation of the appendix. The most common hypothesis is that eggs in the appendix wall stimulate inflammation and thus fibrosis and narrowing of the appendiceal lumen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] The incidence of schistosomal appendicitis is 0.02-6% in endemic areas but its very rare in developed countries. [5,6] Studies where schistosomiasis is endemic, have shown appendicitis to be relatively uncommon and the cause is not usually attributable to a schistosomal infestation of the appendix. The most common hypothesis is that eggs in the appendix wall stimulate inflammation and thus fibrosis and narrowing of the appendiceal lumen.…”
Section: Discussionmentioning
confidence: 99%
“…Morphologically, S. haematobium ova have a terminal spine while S. mansoni have lateral spine. [5,6,7] Some eggs are surrounded by a layer of eosinophilic material, the Splendore-Hoeppli phenomenon. [8] Physicians must be aware of the possibility of seeing atypical presentations of parasitic diseases, especially considering the worldwide increase in immigration and tourism.…”
Section: Discussionmentioning
confidence: 99%
“…13 A more recent study also from Nigeria reported schistosomiasis of the appendix in 4.2% of surgical specimens. 14 In contrast, peritoneal involvement in schistosomiasis seems to be a very rare event. Gali 8 reported only one case of generalized peritonitis in 27 cases of schistosomal appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…10 Others proposed that chronic schistosomal granulamotous inflammation, fibrosis, narrowing of the lumen and swelling of bowel wall may lead to secondary obstruction and acute appendicitis. 9,14 A critical appraisal of the association between schistosomiasis and acute appendicitis is reported from the histological findings characterized by infiltrations of the submucosal and the muscular layer by polymorphonuclear leukocytes, in addition to the presence of schistosome eggs. 14 In the case of schistosomiasis mansoni, intramuscular oviposition (submucosa) may cause an obstructive type of appendicitis with a greater risk of perforation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation